Application of Promotion and Marketing of Micro, Small and Medium Enterprises (Umkm) of Pariaman City (Aplikasi Promosi Dan Pemasaran Hasil Usaha Mikro Kecil Menengah (Umkm) Kota Pariaman) - Romi Hardianto; Yesri Elva; Eva Rianti (Jurnal KomtekInfo, 2019)
Micro, Small and Medium Enterprises (MSMEs) have an important role to support the economy in Indonesia and to enhance the era of the ASEAN free market community (MEA). MSMEs have been spread in almost every region in Indonesia, but MSMEs have been prevented from promoting their business results to the wider community because of promotions that are still carried out by word of mouth, with the existence of e-commerce as a technological development can help this problem. . E-commerce is a dynamic set of technologies, applications and business processes that connect certain companies, consumers and communities through electronic transactions and the electronic, trading of goods, services and information